Locke's Conception of Substemce - Mangrum, Hamilton Earl (My University, 1970)
It is the purpose and intent of this thesis to examine the conception of substance and other notions relevant thereto as expressed in John Locke's An Essay Concerning Human Understanding. It outlines the fundamental epistemological position upon which Locke's conception of substance is based, then critically considers Locke's account of primary and secondary qualities, the central conception of substance, and the attendant notions of essence and abstraction. The concluding chapter is a summarizing of Locke's position and a statement as to the final position of this thesis.
The primary method or technique employed is one of textual analysis. The edition of the Essay which was primarily used was that edited by Alexander Campbell Fraser and published in two volumes (paperback) by Dover Publications, Inc., of New York in 1959.
Keywords: Philosophy; Philosophy